2019
DOI: 10.1016/j.jaapos.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of asymmetrical accommodation on anisometropic amblyopia treatment outcomes

Abstract: The study was conducted at the University of Reading. No competing interests.No financial disclosures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
2
0
0
3
Order By: Relevance
“…consistent with the previous research results (Toor et al, 2019). Hence, this study's findings proposed that anisometropia could lead to abnormal accommodative function, accelerating the development of anisometropia or binocular myopia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…consistent with the previous research results (Toor et al, 2019). Hence, this study's findings proposed that anisometropia could lead to abnormal accommodative function, accelerating the development of anisometropia or binocular myopia.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in Group 2, the AA and AF of the myopic eyes were lower than the emmetropic eyes. These suggested that there was no obvious difference in binocular accommodative function in myopic patients with the same refractive state, but some degree of inequality in the binocular accommodative function of patients with anisometropia was found, consistent with the previous research results ( Toor et al, 2019 ). Hence, this study’s findings proposed that anisometropia could lead to abnormal accommodative function, accelerating the development of anisometropia or binocular myopia.…”
Section: Discussionsupporting
confidence: 91%
“…Нарушение аккомодации у детей с гиперметропией является одним из главных факторов нарушения процесса эмметропизации и поддержания расфокусировки изображения. Наиболее тяжёлые изменения аккомодации наблюдаются у детей с анизометропической амблиопией и гиперметропией, у которых развиваются анизоаккомодация и слабость аккомодации [8]. Для исключения стойких функциональных нарушений и обеспечения полной коррекции у таких детей предпочтительна контактная коррекция.…”
Section: актуальностьunclassified
“…она приблизилась к норме [10]. Опубликованное исследование ученых из Великобритании показало, что у большинства детей с амблиопией высокой степени и анизометропией происходит опережение аккомодации на расстоянии и ее запаздывание на близком расстоянии -антиаккомодация [13].…”
Section: материал и методы исследованияunclassified
“…Принято считать, что аккомодация симметрична в обоих глазах. Но если говорить об анизометропии, то с вероятностью более 80% проявится анизоаккомодация [3].…”
unclassified